Oral lesions in patients infected with SARS-CoV-2: a case series (Research, Society and Development, 2021)
As the COVID-19 pandemic spreads around the world, professionals must prepare for an increase in severely ill patients. Considering that professionals who perform oral care, especially the oral health team, is the most exposed to SARS-CoV-2, and that saliva can be the main vector in the transmission from person to person, it is essential that they are supported by the best evidence for their performance with risk reduction. In view of the literature, the clinical studies of COVID-19 do not often describe oral symptoms, and it is still uncertain whether these manifestations may be a typical clinical pattern resulting from direct SARS-CoV-2 infection or a systemic consequence, given the possibility of co-infections, impaired immune system and adverse drug reactions. As the prevalence of clinical manifestations is still unknown, the possible manifestations of COVID-19 in the oral cavity has been considered of wide and current interest. Therefore de aim of this study was to report a case series of oral lesions in patients infected with SARS-CoV-2.